Analisis Hukum Pemberian Hak Guna Bangunan Di Atas Tanah Hak Pengelolaan Dari Pemerintah Daerah Kabupaten Deli Serdang kepada PT. Kawasan Industri Medan (Persero) - Feri Efendi; Ahmad Fauzi; Alpi Sahari (Iuris Studia: Jurnal Kajian Hukum, 2020)
PT. Medan Industrial Area (Persero) is a state-owned enterprise engaged in industrial estate management services. PT. Medan Industrial Estate (Persero) as management rights holder can submit parts of the land to third parties according to the requirements of management rights holders which cover allotment, use, time period, and compensation with provisions for granting land rights to third parties, especially building usufructuary rights. on land management rights carried out by authorized officials based on legislation. The problem raised in this study, namely how the legal provisions for granting management rights over land from the Regional Government of Deli Serdang Regency to PT. Medan Industrial Area (Persero), the implementation of the surrender of parts of the land from PT. Medan Industrial Area (Persero) to third parties, especially the building rights for land management rights, and the accountability of PT. Medan Industrial Area (Persero) for the management of land rights granted by the Regional Government of Deli Serdang Regency